2022
DOI: 10.1017/dmp.2022.212
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Transmission Potential and Policy Changes in South Carolina, February 2020 – January 2021

Abstract: Introduction: We aimed to examine how public health policies influenced the dynamics of COVID-19 time-varying reproductive number (R t ) in South Carolina from February 26, 2020 to January 1, 2021. Methods: COVID-19 case series (March 6, 2020 - January 10, 2021) were shifted by 9 days to approximate the infection date. We analyzed the effects of state and county policies on R t using EpiEstim. We performed linear regression to evaluate if per-capita cumulative case cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Nine showed an increasing trend in the number of daily new confirmed COVID-19 cases, growth rate or Rt of COVID-19. One study in South Carolina, US, estimated the Rt increased by 12.3% (95% CrI: 10.1%, 14.4%) after schools reopened at the end of August 2020 [ 21 ]. However, one study found that the reopening of schools did not immediately impact SARS-CoV-2 incidence, and an increase in incidence was not observed until 13 weeks after reopening [ 203 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine showed an increasing trend in the number of daily new confirmed COVID-19 cases, growth rate or Rt of COVID-19. One study in South Carolina, US, estimated the Rt increased by 12.3% (95% CrI: 10.1%, 14.4%) after schools reopened at the end of August 2020 [ 21 ]. However, one study found that the reopening of schools did not immediately impact SARS-CoV-2 incidence, and an increase in incidence was not observed until 13 weeks after reopening [ 203 ].…”
Section: Resultsmentioning
confidence: 99%
“…These were carried out at a national and sub-national scale, with nine studies conducted within the first year of the pandemic (electronic supplementary material, appendix C). Ten studies examined the effectiveness of workplace measures using population-level data [ 17 , 21 , 55 , 234 , 236 238 , 240 243 ]. Six studies assessed workplace mobility to explain the variation in the COVID-19 growth rate, case numbers or Rt [ 17 , 55 , 234 , 236 , 237 , 240 ] consistently showed that reduced workplace mobility was significantly associated with reduced SARS-CoV-2 incidence or transmission [ 234 , 236 , 237 , 240 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations